The transcriptional landscape of the giant freshwater prawn: Embryonic development and early sexual differentiation mechanisms - Grinshpan, Nufar; Abayed, Faiza A.A.; Wahl, Melody; Ner-Gaon, Hadas; Manor, Rivka; Sagi, Amir; Shay, Tal (Frontiers in Endocrinology, 2022)
The giant freshwater prawn pjMacrobrachium rosenbergii is one of the best studied species in aquaculture. However, the transcriptional changes associated with embryonic development and the sexual differentiation mechanism of M. rosenbergii remain to be elucidated. To characterize the embryonic development of this prawn and to determine whether differential expression and differential splicing play roles in the early sexual differentiation of M. rosenbergii, we profiled five developmental days of male and female embryos by RNA sequencing. We identified modules of co-expressed genes representing waves of transcription that correspond to physiological processes in early embryonic development (such as the maternal-to-zygotic transition) up to preparation for life outside the egg (development of muscles, cuticle etc.). Additionally, we found that hundreds of genes are differentially expressed between sexes, most of them uncharacterized, suggesting that the sex differentiation mechanism of M. rosenbergii might contain clade-specific elements. The resulting first-of-a-kind transcriptional map of embryonic development of male and female M. rosenbergii will guide future studies to reveal the roles of specific genes and splicing isoforms in the embryonic development and sexual differentiation process of M. rosenbergii.